Composing for the red screen : Prokofiev and Soviet film - Bartig, Kevin (Oxford music/media series., 2013)
Sound film captivated Sergey Prokofiev during the final two decades of his life: he considered composing for nearly two dozen pictures, eventually undertaking eight of them, all Soviet productions. Drawing on newly available sources, Composing for the Red Screen examines - for the first time - the full extent of this prodigious cinematic career.